2010
DOI: 10.1152/jn.00002.2010
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and NT-3 Increase Velocity of Activity Front Propagation in Unidimensional Hippocampal Cultures

Abstract: Jacobi S, Soriano J, Moses E. BDNF and NT-3 increase velocity of activity front propagation in unidimensional hippocampal cultures. J Neurophysiol 104: 2932-2939, 2010. First published July 28, 2010 doi:10.1152/jn.00002.2010. Neurotrophins are known to promote synapse development as well as to regulate the efficacy of mature synapses. We have previously reported that in two-dimensional rat hippocampal cultures, brain-derived neurotrophic factor (BDNF) and neurotrophin-3 significantly increase the number of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The contrasting velocities of activity propagation in the tracks configuration, with measured velocities about 5 times larger along tracks than across them, can be put in context of theoretical models 51 , 52 and experiments on activity propagation in one-dimensional neuronal cultures. 53 , 54 , 55 These studies revealed that the velocity of activity fronts depended on average neuronal connectivity and synaptic strength. If we assume that synaptic strength is similar in all neurons in the culture, then we conclude that connectivity along tracks was 5-fold higher than transverse to it.…”
Section: Discussionmentioning
confidence: 96%
“…The contrasting velocities of activity propagation in the tracks configuration, with measured velocities about 5 times larger along tracks than across them, can be put in context of theoretical models 51 , 52 and experiments on activity propagation in one-dimensional neuronal cultures. 53 , 54 , 55 These studies revealed that the velocity of activity fronts depended on average neuronal connectivity and synaptic strength. If we assume that synaptic strength is similar in all neurons in the culture, then we conclude that connectivity along tracks was 5-fold higher than transverse to it.…”
Section: Discussionmentioning
confidence: 96%
“…The contrasting velocities of activity propagation in the tracks configuration, with measured velocities about 5 times larger along tracks than across them, can be put in context of theoretical models (Bressloff, 2000; Golomb and Ermentrout, 1999) and experiments on activity propagation in one-dimensional neuronal cultures (Feinerman et al, 2005; Jacobi et al, 2010; Jacobi and Moses, 2007). These studies revealed that the velocity of activity fronts depended on average neuronal connectivity and synaptic strength.…”
Section: Discussionmentioning
confidence: 99%
“…An idea that was particularly enlightening was the study of the velocity of propagating fronts. Some years ago, we showed experimentally and theoretically that the velocity of activity propagation depends on the average connectivity of the neurons and the balance between excitation and inhibition [62]. Thus, such a velocity analysis provides an elegant way to obtain indirect information on the connectivity of the network and its changes upon development or pharmacological action.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%